Bioethics and biobanking in biomedical research in Malaysia - Abdul Rahman, Suzanah (International Islamic University Malaysia, 2025)
In the rapidly evolving domain of biomedical research, bioethics is a critical pillar that ensures the alignment of scientific advancements to ethical principles, societal values and human rights. The systematic collection of biological samples, processing and storage involved in precision medicine, epidemiological research and genetic studies are in need of a robust ethical governance and careful navigation in the biobanking practice. Addressing bioethical concerns is crucial, as Malaysia progresses to become one of the leaders in biomedical innovation. Discussions and the establishment of various ethical frameworks and national guidelines throughout the years have demonstrated Malaysia’s commitment towards improving ethical oversights, regulatory clarity, and public trust in biomedical research and biobanking practices. However, challenges in areas such as informed consent, data privacy, equitable sharing of benefits and public trust in research institutions persist.